2022
DOI: 10.1093/toxsci/kfac120
|View full text |Cite
|
Sign up to set email alerts
|

TCDD alters essential transcriptional regulators of osteogenic differentiation in multipotent mesenchymal stem cells

Abstract: Differentiation of multipotent mesenchymal stem cells into bone-forming osteoblasts requires strict coordination of transcriptional pathways. Aryl hydrocarbon receptor (AhR) ligands, such as 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD), have been shown to alter osteoblast differentiation in vitro and bone formation in multiple developmental in vivo models. The goal of the present study was to establish a global transcriptomic landscape during early, intermediate, and apical stages of osteogenic differentiation i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…The regulatory network of TF‐hub gene revealed that FAM129A and RNF24 could be regulated by POU2F2 and FOXC1. POU2F2 was shown to be an important transcription factor during the differentiation of MSCS into osteoblasts, 31 and FOXC1 was considered to be an important gene for bone marrow stem cell migration and adhesion to cortical bone. 32 , 33 This regulatory network provides a direction for future research into the role and regulatory mechanisms of FAM129A and RNF24 in OP.…”
Section: Discussionmentioning
confidence: 99%
“…The regulatory network of TF‐hub gene revealed that FAM129A and RNF24 could be regulated by POU2F2 and FOXC1. POU2F2 was shown to be an important transcription factor during the differentiation of MSCS into osteoblasts, 31 and FOXC1 was considered to be an important gene for bone marrow stem cell migration and adhesion to cortical bone. 32 , 33 This regulatory network provides a direction for future research into the role and regulatory mechanisms of FAM129A and RNF24 in OP.…”
Section: Discussionmentioning
confidence: 99%
“…Recent work by Behan Bush et al demonstrated the toxicity of xenobiotics Aroclor and Non-Aroclor mixtures of Polychlorinated Biphenyl exposure on Human Adipose MSCs (74). Another recent study has demonstrated that 2,3,7,8tetrachlorodibenzo-p-dioxin alters essential transcriptional regulators of osteogenic differentiation in bone marrow MSCs (75). Our present study further strengths this concept by molecular profiling of MSCs in their innate/native (Metabolic activity, Immunomodulatory secretome, Angiogenic secretome) and responsive functionality (Exogenous IFNg induced secretome, cell surface molecules, phosphorylation signals) post Atrazine exposure.…”
Section: Discussionmentioning
confidence: 99%